2022
DOI: 10.21037/jgo-21-866
|View full text |Cite
|
Sign up to set email alerts
|

Combined screening analysis of aberrantly methylated-differentially expressed genes and pathways in hepatocellular carcinoma

Abstract: Background: Methylation plays an important role in hepatocellular carcinoma (HCC) by altering the expression of key genes. The aim of this study was to screen the aberrantly methylated-differentially expressed genes (DEGs) in HCC and elucidate their underlying molecular mechanism.Methods: Gene expression microarrays (GSE101685) and gene methylation microarrays (GSE44909) were selected. DEGs and differentially methylated genes (DMGs) were screened. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This study emphasizes another possible pathway involved in KIF11 in HCC [ 43 ]. Lastly, Cao and coworkers found that KIF11 overexpression in HCC could also be related to epigenetic modifications, such as DNA methylation; in fact, among the genes exhibiting hypomethylation KIF11 is included, confirming once again the strong relationship between Eg5 expression and HCC and shedding light on another possible mechanism able to explain this correlation [ 42 ].…”
Section: Eg5 In Tumor Onset and Progressionmentioning
confidence: 94%
“…This study emphasizes another possible pathway involved in KIF11 in HCC [ 43 ]. Lastly, Cao and coworkers found that KIF11 overexpression in HCC could also be related to epigenetic modifications, such as DNA methylation; in fact, among the genes exhibiting hypomethylation KIF11 is included, confirming once again the strong relationship between Eg5 expression and HCC and shedding light on another possible mechanism able to explain this correlation [ 42 ].…”
Section: Eg5 In Tumor Onset and Progressionmentioning
confidence: 94%
“…Top five items were selected. et al30 , 13 from Jiang et al31 , 20 from Zhang et al32 , 12 from Wu et al33 , 5 from Nguyen et al34 , 15 from Zhou et al35 , 6 from Yu et al36 , 10 from Kakar et al37 , 10 from Ji et al38 , 11 from Chen et al39 , 10 from Qiang et al40 , 10 from Wang et al41 , 10 from Zhang et al42 , 14 from Kim et al43 , 10 from Zhang et al44 , 14 from Sha et al45 , 10 from Chen et al46 , 4 from He et al47 , 10 from Zhang et al48 , 4 from Hu et al49 , 9 from Zhang et al50 , 15 from Li et al51 , 5 from Cao et al52 , 7 from Yang et al53 , 5 from Wang et al54 , 9 from Jiang et al55 , 16 from Li et al56 , 15 from Xing et al…”
mentioning
confidence: 99%